Philosophers and the Jewish Bible - Manekin, Charles Harry (Studies and texts in Jewish history and culture, 2008)
Speaking about God: Bahya as biblical exegete / Diana Lobel -- The dual nature of the biblical angel in the philosophy of Maimonides / Hannah Kasher -- The hermeneutics of order in medieval Jewish philosophical exegesis / Robert Eisen -- Ambiguities of scriptural exegesis: Joseph ibn Kaspi on God's foreknowledge / Charles H. Manekin -- Spinoza, history, and Jewish modernity / Michael A. Rosenthal -- What Maimonides can teach us about reading the Bible / Kenneth Seeskin -- Jacob and Isaac: a tale of deception and self-deception / Charlotte Katzoff -- God's project / Jerome M. Segal -- Samson and self-destroying evil / Eleonore Stump -- Against theology / Howard Wettstein